Would "Cold Turkey" Work in Turkey? - Gelos, R. (IMF Working Papers; Working Paper ;, 2003)
Persistently high inflation rates have led many to believe that inflation in Turkey has become "inertial," posing an obstacle to disinflation. We assess the empirical validity of this argument. We find that the current degree of inflation persistence in Turkey is lower than in Brazil and Uruguay prior to their successful stabilization programs. More significantly, expectations of future inflation are more important than past inflation in shaping the inflation process, providing little evidence of "backward-looking" behavior. Using survey data, we find that inflation expectations, in turn, depend largely on the evolution of fiscal variables.